Breath methane and large bowel cancer risk in contrasting African populations. Issue 5 (May 1988) - Segal, I; Walker, A R; Lord, S; Cummings, J H
Abstract : Breath methane has been measured in 1016 people from four populations resident in Southern Africa which experience widely different risks of bowel cancer and other colonic diseases. Highly significant differences in the proportion of subjects with detectable methane in breath were found; % producers–rural black 84, urban black 72, white 52, Indian 41 (chi 2 121 p less than 0.001 3 df). There was a slight preponderance of female producers over male (female producers 63%, males 57%) and an age trend with fewer producers in the older age groups in the urban blacks and Indians, these comparisons being significant when tested by stepwise logistic regression analysis. Bowel cancer risk, determined from a variety of sources, was lowest in rural blacks, greatest in whites, with intermediate rates for urban blacks and Indians. Methane production in the human colon shows significant interethnic differences but which bear no relation to bowel cancer risk in these populations.